Tackling consumer vulnerability in energy and banking: towards a new approach. Issue 2 (3rd April 2018) - Graham, Cosmo
Abstract: This article examines the new approach to vulnerability developed by Ofgem and the Financial Conduct Authority to see whether it has been implemented at company level and had an impact on the ombudsman. It sets out the context within which this approach has been developed and then looks at its implementation through two case studies. The main lesson from these case studies is that establishing a broad concept of vulnerability, as has been argued for in the academic literature, is just a first step. Operationalising the concept presents major challenges especially in the context of systems dealing with large numbers of consumers.